Knowledge of young men about testicular cancer - Maria Mika; Natalia Miś; Małgorzata Kołpa (University of Applied Sciences in Tarnow, Poland, 2017)
Introduction: Testicular cancer is a cancer of male reproduction system, with a morbidity rate of 1,5%. Testicular cancer is common among young men. Aim of the paper: Aim of the paper was to present the young men's knowledge about testicular cancer. Material and methods: The results were taken by the author's questionnaire and by MHLC through the diagnostic survey. 200 men, aged 18 - 35, took part in the survey. Results: Results indicate that only few men declared that they know a) how to self-examin themselves in terms of the testicular cancer; b) the age of the most common testicular cancer's occurrence. Conclusions: The level of knowledge among young men is disappointing, irrespectively of age, education, and social status.